1994
DOI: 10.1080/00071669408417702
|View full text |Cite
|
Sign up to set email alerts
|

Replacement value of blue‐green alga(spirulina platensis)for fishmeal and a vitamin‐mineral premix for broiler chicks

Abstract: 1. The effect of sun-dried Spirulina platensis in poultry diets was studied in a 12-week feeding trial by replacing either fishmeal (FM) or groundnut cake (GC) in a commercial diet with algae at isonitrogenous concentrations of 140 g/kg and 170 g/kg respectively. Additional vitamins/minerals were omitted from the algal diets because Spirulina is rich in them. 2. Efficiency of food utilisation, protein efficiency ratio and dressing percentage indicated that substitution of FM or GC by alga did not affect the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 9 publications
9
32
0
2
Order By: Relevance
“…Therefore, we hypothesised that the relative organ weight of the broilers could be affected by the microalgae supplementation. The results were out of anticipation, which is in agreement with Venkataraman et al (1994), who reported that the sun-dried Spirulina platensis algae supplementation did not affect the organ weight in broilers.…”
Section: Blood Profiles and Relative Organ Weightsupporting
confidence: 82%
“…Therefore, we hypothesised that the relative organ weight of the broilers could be affected by the microalgae supplementation. The results were out of anticipation, which is in agreement with Venkataraman et al (1994), who reported that the sun-dried Spirulina platensis algae supplementation did not affect the organ weight in broilers.…”
Section: Blood Profiles and Relative Organ Weightsupporting
confidence: 82%
“…Mortality was very low (only one bird in the control group died) and therefore did not differ (P >0.05) among groups. These results are in agreement with those of previous researchers (Ross & Dominy, 1990;Venkataraman et al, 1994;Qureshi et al, 1996;Gongnet et al, 2001;Toyomizu et al, 2001), who recorded nonsignificant effects of dietary spirulina supplementation on performance parameters, although it has been reported that spirulina inclusion over 100 g/kg could depress the birds' growth (Ross & Dominy, 1990). In contrast, other researchers (Kharde et al, 2012;Shanmugapriya & Saravana Babu, 2014) reported that dietary spirulina significantly improved weight gain and feed efficiency of chickens compared with the control groups.…”
Section: Resultssupporting
confidence: 36%
“…The same response was also reported by Danny et al (2016), where using 1, 2, and 4% of dietary spirulina led to an improved growth performance than that of the control, while using higher levels resulted in adverse effects. On the contrary, Venkataraman et al (1994) found that using high levels of dietary spirulina 14-17% did not affect broiler performance or meat quality. During the laying period, the Spirulina birds (T1 and T2) had higher final BWs than that of the control group.…”
Section: Egg Quality Parametersmentioning
confidence: 68%